Leadless pacemaker: State of the art and incoming developments to broaden indications. Issue 12 (29th November 2020) - Curnis, Antonio; Salghetti, Francesca; Cerini, Manuel; Fabbricatore, Davide; Ghizzoni, Giulia; Arrigoni, Luca; Generati, Greta; Arabia, Gianmarco; Maiolo, Vincenzo; Aboelhassan, Mohamed; Bontempi, Luca
Abstract: Theleadless pacemaker (LLPM) therapy has been developed in recent years to overcome the transvenous lead and device pocket‐related complications. The LLPMs now available are self‐contained right ventricular pacemakers and are limited to single‐chamber ventricular pacing modality. This literature review deals with the current status of LLPM technology and current areas of clinical applicability. The safety and efficacy outcomes published from randomized clinical trials and real world registries are analyzed and compared with historical conventional transvenous pacemaker data. Furthermore, new pacing modalities and future perspectives to broaden the clinical use and cover most of pacing indications are discussed. Due to the overall safe and effective profile in the short term and intermediate term, also in fragile patients, the LLPM use is constantly growing in daily clinical practice. Actually, it can be considered a landmark innovation, through which a new era of cardiac pacing has begun.